Development of a Model for Predicting Dynamic Response of a Sphere at Viscoelastic Interface: a Dynamic Hertz Model - Körük, Hasan (IOP Publishing Ltd, 2021)
A model for predicting the dynamic response of a sphere at viscoelastic interface is presented. The model is based on Hertz contact model and the model for a sphere in a medium.In addition to the elastic properties of medium and the size of sphere, the model considers thedensity of sphere, the density and viscosity of medium, and damping of oscillations of spheredue to radiation of shear waves. The model can predict not only the effects of the mechanicalproperties of medium, the physical properties of sphere, and the amplitude of excitation forceon sphere displacement, but also the effects of these parameters on shift of resonancefrequency. The proposed model can be used to identify the elastic and damping properties ofmaterials, and to understand the dynamic responses of spherical objects at viscoelasticinterfaces in practical applications.